Risk Screening of Veterans Throughout the Life Course. (2nd March 2022) - VanTil, L. D.; MacLean, M. B.; Coulthard, J.; Murray, R.; Lourenso, S.; Camarda, J.; Lea, T.
Abstract: Both the Canadian Armed Forces and Veterans Affairs Canada identified the need for a brief standardized tool to screen military members and veterans for the risk of a difficult adjustment to civilian life, frailty, suicide and homelessness. Data from Life After Service Studies ( n  = 8, 101) were used to build logistic regression models of difficult adjustment to civilian life. The resulting brief risk screener was piloted in 2018 ( n  = 246). The modeling considered 28 risk indicators, used 17 of these to build the models, and maintained 8 questions for a brief risk screener. Optimal cutoff was found with a threshold of 3+ for difficult adjustment to civilian life, with 39% sensitivity (95% CI: 37.9 to 41.1) and 94% specificity (95% CI: 93.1 to 94.6). A longer 10 item questionnaire was implemented. Pilot participants who were help-seeking veteran clients had frequency by risk level of 42% low, 40% moderate, and 18% high. Pilot participants who were serving military members had frequency by risk level of 79% low, 13% moderate, and 8% high. In 2019, Canadian government implemented a new standardized risk screening tool to improve the effectiveness of services and referrals.